Usability of iron (II)-hydrogen peroxide in the COD reduction of a strong wastewater - (:unkn) unknown (Parlar Scientific Publications, 1993)
The hydrogen peroxide-iron(II) system was used to hydroxylate and to oxidize the refractory organic materials in a strong wastewater with mean COD of 14000. The relations between the COD of water and the reagents were established to get higher COD removal yields.
Keywords: COD removal; Hydrogen peroxide; Iron(II); Oxydation; Pharmaceutical wastewater